Traditional uses of wild and tended plants in maintaining ecosystem services in agricultural landscapes of the Eastern Cape Province in South Africa - Alfred Maroyi (BMC, 2022)
Abstract Background Many communities in developing countries rely on ecosystem services (ESs) associated with wild and cultivated plant species. Plant resources provide numerous ESs and goods that support human well-being and survival. The aim of this study was to identify and characterize wild and tended plant species, and also investigate how local communities in the Eastern Cape Province in South Africa perceive ESs associated with plant resources. Methods The study was conducted in six local municipalities in the Eastern Cape Province, between March 2016 and September 2021. Data on socio-economic characteristics of the participants, useful plants harvested from the wild and managed in home gardens were documented by means of questionnaires, observation and guided field walks with 196 participants. The ESs were identified using a free listing technique. Results A total of 163 plant species were recorded which provided 26 cultural, regulating and provisioning ESs. Provisioning ESs were the most cited with at least 25 plant species contributing towards generation of cash income, food, traditional and ethnoveterinary medicines. Important species recorded in this study with relative frequency of citation (RFC) values > 0.3 included Alepidea amatymbica, Allium cepa, Aloe ferox, Artemisia afra, Brassica oleracea, Capsicum annuum, Cucurbita moschata, Hypoxis hemerocallidea, Opuntia ficus-indica, Spinacia oleracea, Vachellia karroo and Zea mays. Conclusion Results of this study highlight the importance of plant resources to the well-being of local communities in the Eastern Cape within the context of provision of essential direct and indirect ESs such as food, medicinal products, construction materials, fodder, regulating, supporting and cultural services. The ESs are the basis for subsistence livelihoods in rural areas, particularly in developing countries such as South Africa. Therefore, such body of knowledge can be used as baseline data for provision of local support for natural resource management initiatives in the province and other areas of the country.